Effects of rain and other phenomena on the received signal of the inmarsat earth-space system - Ong, Jin Teong. (2008)
The records of signals from the inmarsat satellite received at low elevation angle at the Singapore Telecom Earth Station at Sentosa were studied to determine the cause of significant fading which had occurred. The three main mechanisms were identified as rain attenuation, ionospheric scintillations, and troposheric effects.